Lifestyle decisions and climate mitigation: current action and behavioural intent of youth - Pickering, Gary J.; Schoen, Kaylee; Botta, Marta (Mitigation and adaptation strategies for global change, 2021)
Youth carry the burden of a climate crisis not of their making, yet their accumulative lifestyle decisions will help determine the severity of future climate impacts. We surveyed 17–18 year old’s ( N = 487) to establish their action stages for nine behaviours that vary in efficacy of greenhouse gas emission (GGE) reduction and the explanatory role of climate change (CC) knowledge, sociodemographic and belief factors. Acceptance of CC and its anthropogenic origins was high. However, the behaviours with the greatest potential for GGE savings ( have no children/one less child, no car or first/next car will be electric, eat less meat ) have the lowest uptake. Descriptive normative beliefs predicted intent to adopt all high-impact actions, while environmental locus of control, CC scepticism, knowledge of the relative efficacy of actions, religiosity and age were predictive of action stage for several mitigation behaviours (multinomial logistic regression). These findings inform policy and communication interventions that seek to mobilise youth in the global climate crisis response.